A contribution to study of deep bed filtration using wound cartridge filters, Part I: Mathematical model - Crha, Břetislav; Cakl, Jiří; Doleček, Petr; Machač, Ivan (Univerzita Pardubice, 1995)
A quantitative relationship between the pressure drop of a clogged cylindrical fibrous filter bed and the extent of particle deposition is presented. The starting point is the modified model of the flow through filtration medium which combines the tube flow and flow around solid bodies. The effect of particle deposition is assumed to increase the fibre diameter and to decrease the local porosity. To complete the description, the macroscopic conservation equation and the deposition rate equation are also specified. The method of solution of these equations, which yields the values of effluent concentration, specific deposit, and pressure as functions of time and position, is also proposed and discussed.